The rate-limiting step in yeast PGK1 mRNA degradation is an endonucleolytic cleavage in the 3'-terminal part of the coding region. - Vreken, P (1992)
Insertion of an 18-nucleotide-long poly(G) tract into the 3'-terminal untranslated region of yeast phosphoglycerate kinase (PGK1) mRNA increases its chemical half-life by about a factor of 2 (P. Vreken, R. Van der Veen, V. C. H. F. de Regt, A. L. de Maat, R. J. Planta, and H. A. Raué, Biochimie 73:729-737, 1991). In this report, we show that this insertion also causes the accumulation of a degradation intermediate extending from the poly(G) sequence down to the transcription termination site. Reverse transcription and S1 nuclease mapping experiments demonstrated that this intermediate is the product of shorter-lived primary fragments resulting from endonucleolytic cleavage immediately downstream from the U residue of either of two 5'-GGUG-3' sequences present between positions 1100 and 1200 close to the 3' terminus (position 1251) of the coding sequence. Similar endonucleolytic cleavages appear to initiate degradation of wild-type PGK1 mRNA. Insertion of a poly(G) tract just upstream from the AUG start codon resulted in the accumulation of a 5'-terminal degradation intermediate extending from the insertion to the 1100-1200 region. RNase H degradation in the presence of oligo(dT) demonstrated that the wild-type and mutant PGK1 mRNAs are deadenylated prior to endonucleolytic cleavage and that the half-life of the poly(A) tail is three- to sixfold lower than that of the remainder of the mRNA. Thus, the endonucleolytic cleavage constitutes the rate-limiting step in degradation of both wild-type and mutant PGK1 transcripts, and the resulting fragments are degraded by a 5'----3' exonuclease, which appears to be severely retarded by a poly(G) sequence.